Back Cover: Electrochemical Synthesis of One‐Dimensional Mesoporous Pt Nanorods Using the Assembly of Surfactant Micelles in Confined Space (Angew. Chem. Int. Ed. 31/2013). Issue 31 (15th July 2013) - Li, Cuiling; Sato, Takaaki; Yamauchi, Yusuke
<x xml:space="preserve">Abstract</x> Self‐supported platinum nanorods with a high density of mesopores are prepared by electrochemical assembly of platinum‐containing micelles in the pores of a polycarbonate membrane. In their Communication on page 8050 ff., Y. Yamauchi et al. show that superior tolerance towards carbon monoxide can be realized in the oxidation reaction of methanol by using the platinum nanorods as electrocatalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>